2011
DOI: 10.1589/jpts.23.683
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Plantar Foot Pressure and COP between Flat and Normal Feet During Walking

Abstract: Abstract.[Purpose] The purpose of this study was to compare the peak plantar foot pressure and the pathway of the center of pressure (COP) between normal and flat feet. [Subjects and Methods] Nineteen subjects (10 normal feet, 9 flat feet) participated in this study. Plantar foot pressure was recorded by the Matscan system (Tekscan, Boston, USA) while walking upright. Plantar foot surface was divided into seven regions for pressure measurement: two toe regions, three forefoot regions, one midfoot region, and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 30 publications
6
18
0
1
Order By: Relevance
“…However, there is lack of scientific studies Regarding the correlation between the position of foot axis and heel valgus, we found significant difference in the group with unilateral valgus heel position where the foot axis was rotated more medially in the limb with valgus heel position. This correlates with the results of Han et al (2011), which states medial foot deviation in the flatfoot. However, the authors presented the results concerning bilateral valgus and non-valgus groups.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, there is lack of scientific studies Regarding the correlation between the position of foot axis and heel valgus, we found significant difference in the group with unilateral valgus heel position where the foot axis was rotated more medially in the limb with valgus heel position. This correlates with the results of Han et al (2011), which states medial foot deviation in the flatfoot. However, the authors presented the results concerning bilateral valgus and non-valgus groups.…”
Section: Discussionsupporting
confidence: 91%
“…Ledoux and Hillstrom (2002) found increased loading below the big toe in bilateral valgus heel position, with general overloading of the first foot ray. Han et al (2011) found significant reduction in foot loading in the fourth and fifth metatarsals and in the lateral part of the heel in bilateral flatfoot. Their conclusion correlates with the results of our study.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…As the foot determines the base of support geometry and dynamic variability of CoP, foot problems can affect CoP path and parameters (6-9). Furthermore, as CoP is the mean of all pressures applied to the plantar surface of the foot, any deformity in foot shape can alter its path and parameters (8, 10, 11).…”
Section: Introductionmentioning
confidence: 99%